Is chloroplast movement in tobacco plants influenced systemically after local illumination or burning stress? - Naus, Jan; Rolencová, Monika; Hlavácková, Vladimíra (Journal of integrative plant biology, 2008)
Chloroplast movement has been studied in many plants mainly in relation to the local light, mechanical or stress effects. Here we investigated possible systemic responses of chloroplast movement to local light or burning stress in tobacco plants (Nicotiana tabacum cv. Samsun). Chloroplast movement was measured using two independent methods: one with a SPAD 502 Chlorophyll meter and another by collimated transmittance at a selected wavelength (676 nm). A sensitive periodic movement of chloroplasts was used in high or low (2 000 or 50 micromol/m(2) per s photosynthetically active radiation, respectively) cold white light with periods of 50 or 130 min. Measurements were carried out in the irradiated area, in the non-irradiated area of the same leaf or in the leaf located on the stem below the irradiated or burned one. No significant changes in systemic chloroplast movement in non-irradiated parts of the leaf and in the non-treated leaf were detected. Our data indicate that chloroplast movement in tobacco is dependent dominantly on the intensity and spectral composition of the incident light and on the local stimulation and state of the target tissue. No systemic signal was strong enough to evoke a detectable systemic response in chloroplast movement in distant untreated tissues of tobacco plants.
Keywords: Fires; Plant Leaves; světlo; tabák; chloroplasty; požáry; Nicotiana; Light; listy rostlin; Chloroplasts